An Integrative Informatics Approach to Explain the Mechanism of Action of N1-(Anthraquinon-2-yl) Amidrazones as BCR/ABL Inhibitors - Sabbah, Dima A.; Hajjo, Rima; Sweidan, Kamal; Zhong, Haizhen A. (Current Computer - Aided Drug Design, 2021)
Background: Drugs incorporating heterocyclic chemical skeletons possess a plethora of therapeutic activities such as anticancer, antimicrobial, antihypertensive, and antipsychiatric effects. It is becoming routine, nowadays, to use cheminformatics and bioinformatics methods to elucidate the mechanism(s) of action of such drugs. Objective: This study aimed to probe the activity of a recently published series of N1- (anthraquinon-2-yl) amidrazone piperazine derivatives employing computational strategies[1], identify their structural basis of binding to BCR/ABL kinase domain, and explain their anticancer activities in human breast adenocarcinoma (MCF-7) and chronic myelogenous leukemia (K562) cell lines. Methods: We applied an in silico integrative informatics approach integrating molecular descriptors, docking studies, cheminformatics, and network analysis. Results: Our results highlighted the possible involvement of the BCR/ABL and DRD2 pathways in the anticancer activity of the studied compounds, and induced fit docking (IFD) indicated that the BCR/ABL kinase domain is a putative drug target. Additionally, high-scoring docking poses identified a unique network of hydrogen bonding with amino acids Y253, K271, E286, V299, L301, T315, M318, I360, R362, V379, and D3810. Conclusion: Using an integrative informatics approach to characterize our anticancer compounds, we were able to explain the biological differences between synthesized and biologically validated amidrazone piperazine anticancer agents. We were also able to postulate a mechanism of action of this novel group of anticancer agents.
Keywords: chemical-protein interactions